Made in Academia: The Effect of Institutional Origin on Inventors’ Attention to Science - Bikard, Michaël (Organization Science, 2018)
Inventors cannot exploit new scientific discoveries if they do not pay attention to them. However, allocating attention to science is difficult because the scientific literature is complex, vast, fast-changing, and often unreliable. Inventors are therefore likely to rely on informational cues when screening new publications. I posit that inventors pay significantly less attention to discoveries “made in academia” than to those “made in industry” because they believe that the work of academic scientists will be less useful to them. I test this proposition by examining inventors’ patent references to the scientific literature in the case of simultaneous discoveries made by at least one team based in academia and another based in industry. I find that inventors are 23% less likely to cite the academic paper than its “twin” from industry. My results highlight the importance of inventors’ attention as a previously underexplored bottleneck shaping the translation of science into new technologies.